PENGARUH PENGAWASAN DAN MOTIVASI TERHADAP KINERJA GURU - Udin Wahyudin (Pascasarjana Unviersitas Majalengka, 2020)
This research is motivated by the low teacher performance, which is estimated to be the impact of ineffective supervision and low teacher motivation. In educational units, teacher performance is a determining factor for the quality of graduates so that it becomes a central issue in efforts to improve the quality of education. This study aims to identify and analyze: a) teacher supervision, motivation, and performance; b) the effect of supervision on teacher performance; c) the influence of motivation on teacher performance; and d) the effect of supervision and motivation on teacher performance together. The research method used was a survey with a quantitative approach. Sample of 48 people determined by the formula Slovin, data collected through a questionnaire. The analysis design uses descriptive and subjective analysis. Data analysis used statistics, with the help of a computer-assisted calculation of the SPSS program. The results showed that descriptively, supervision, motivation, and teacher performance were in good condition according to respondents' perceptions. In terms of: a) Supervision affects teacher performance by 52,99%; b) motivation has an effect on teacher performance by 47,05%; c) supervision and motivation together have an effect on teacher performance by 59.60%. Conclusion, both individually and collectively, supervision and motivation have an effect on teacher performance